Play with Butterfly: Case Study of Project-Based Learning in Thammissalam Preschool Thailand - Sulyandari, Ari Kusuma; Dewi, Mutiara Sari; Rodtian , Abeedah (JEA (Jurnal Edukasi AUD), 2024)
This article explores the role of play in early childhood education, specifically in the context of project-based science learning at Thammissalam Kindergarten in Thailand. Playing is considered important because it helps develop children's concentration, creativity, motor skills, and cognitive development. Project-based learning is seen as an effective approach to integrating science education into the curriculum, stimulating children's critical and creative thinking. This research uses a qualitative, case study type. Data was taken at Thammissalam Kindergarten, Thailand. We made observations on children in Thammissalam Thailand when the project was carried out. We conducted interviews with teachers and the headmaster about this project. This project was carried out for 1 year. The result of this project is that children understand scientific and cognitive processes because they know the growth of butterflies from the beginning of metamorphosis. Children learn to manage their emotions because they understand that this project will not last for a short time. They also learn cooperation because butterflies need a home. They prepared it all. The project can be implemented in the classroom in stages, for example, when children see caterpillars, they will learn about caterpillars, what caterpillars eat, and how caterpillars move to practice gross motor skills. Maybe it could be researched more deeply about evaluating the long-term effects of project-based learning on child development. Measuring the lasting impact of project-based learning on children's cognitive, social, and emotional development over the longer term. It can also be related to technology. Explore how technology can enhance children's engagement and learning in a project context. It can also be researched further on the differences between using technology and not.